Modified friction stir clinching with protuberance-keyhole levelling: A process for production of welds with high strength. (May 2019) - Paidar, Moslem; Ojo, Olatunji Oladimeji; Moghanian, Amirhossein; Karapuzha, Amal Shaji; Heidarzadeh, Akbar
Abstract: Modified friction stir clinching (MFSC) with protuberance-keyhole leveling approach is employed in joining dissimilar AA2024-T3/AA7075-T6 Al alloys. This technique is a two-step approach where friction stir clinching is established in the first step while the inherent step-like (protuberance-keyhole cavity) is eliminated in the second step. The microstructure, mechanical properties and fracture mode of the MFSC joints are examined and compared with that of the conventional keyhole friction stir spot welds. The results reveal that the new approach eliminates the formation of hook defect while geometric-differential flow-induced defects are formed in the joint. Protuberance and shoulder indentation refilling processes form flow-induced defects at the weld center and at the circumferential shoulder edges respectively. The severity of these defects is reduced via better inter-mixing and flowability at high tool rotational speed. Atomic diffusion induces the formation of Al2 CuMg and Mg2 Si phases in the joints (stir zones). A rise in tool rotational speed increases the tensile-shear and cross-tension loads of the joint from 6798 N to 9487 N and 4366 N to 6850 N respectively. The new joining process improved the joint quality due to enhanced effective bonded/shear area as compared to that of the conventional keyhole friction stir spot welded joint.